Analysis of the Effectiveness of Influencer Marketing, Content Marketing, and Online Advertising Marketing on Purchasing Decisions on the E-Commerce Tik-Tok Shop - Amaliyah, Fitrotul; Indayani, Lilik; Yani, Muhammad (Journal of Economics Education and Entrepreneurship, 2025)
This study aims to determine the extent of the effectiveness of using Influencer Marketing, Content Marketing and Online Advertising Marketing on Purchasing Decisions on E-Commerce Tik-Tok Shop. This study uses a quantitative research method, the data is obtained from 96 respondents by distributing questionnaires given to respondents in the form of a list of questions and then processed using SmartPLS software. Respondents in this study were Tik-Tok users who used the Tik-Tok Shop service. This study shows that there is a strong and significant influence on the effectiveness of using Influencer Marketing, Content Marketing and Online Advertising marketing on Purchasing Decisions on E-Commerce Tik-Tok Shop.